Upaya Meningkatkan Minat Belajar Siswa Melalui Layanan Konseling Kelompok - Fakhrudin Mutakin (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2018)
This research aims to improve MTs students’ learning interest at Al. Ma’arif  Wuluhan class Vll C through group counseling services with 30 students being studied. The data collection methods used were Observation and Questionnaire, which were then analyzed using descriptive data analysis. Based on the results of the initial observation by giving a questionnaire and obtaining the main data with the percentage of learning interest is 33,3% of 30 students, after being given action in the first cycle, the learning interest inceased with a percentage of 55% of 20 students, after continuing in cycle II the level of students’ learning interest increased with a percentage of 88,8% of 9 students. Providing group counseling services shows that students’ learning interest in schools has increased. Research avtivities have been categorized as successful becauce they reach a percentage above the success indicators that have been set at 80% they percentage of students’ interest in learning at school.  Keywords: group counseling, learning interest.